Intersectionality Between the Experiences and Perceptions of Middle-aged Female Government Employees on Pre-menopausal Symptoms and Societal-workplace Discrimination - Marietta. S Santos (Utan Kayu Publishing, 2026)
The pre-menopausal stage involves natural hormonal and physical changes in middle-aged women, affecting both their physical and mental health. Despite its medical basis, misconceptions often fuel discrimination. This bias can appear in healthcare, workplaces, and society, varying by culture and region. Employing a qualitative research method with a narrative analysis design, this study aims to attain the following: (i) explore how middle-aged female government employees see the impact of pre-menopausal symptoms on their daily lives, well-being, and work performance; and (ii) explore how the narratives of middle-aged female government employees reveal the intersectionality of societal and workplace factors in shaping experiences of discrimination during the pre-menopausal stage. The study concludes that middle-aged female government employees face challenges that severely impact their daily functioning and career sustainability, underscoring the urgent need for comprehensive workplace policies, cultural change, legal protections, and supportive programs. In response, recommendations include establishing flexible work accommodations, launching education and training initiatives to reduce stigma, and piloting comprehensive wellness programs through an extension project tailored to this population to improve health outcomes and workplace inclusion.